Assessment of transmission risk in WSSV‐infected shrimp Litopenaeus vannamei upon cooking. Issue 4 (11th February 2020) - Aranguren Caro, Luis Fernando; Mai, Hung N.; Nunan, Linda; Lin, Joshua; Noble, Brenda; Dhar, Arun K.
Abstract: White spot syndrome virus has been a threat to the global shrimp industry since it was discovered in Taiwan in 1992. Thus, shrimp‐producing countries have launched regulations to prevent import of WSSV‐infected commodity shrimp from endemic areas. Recently, cooked shrimp that is infected with WSSV tested positive by PCR. However, there is no study to determine the infectivity of WSSV in cooked shrimp that tested positive by PCR. In the present study, WSSV‐infected shrimp were cooked at boiling temperature for different times including 0, 1, 3, 5, 10 and 30 min. Upon exposure to boiling temperature, WSSV‐infected shrimp were fed to SPF shrimp ( Litopenaeus vannamei ). The result showed experimentally challenged shrimp from 0‐min treatment (positive control) indeed got infected with WSSV. However, experimentally challenged shrimp that were fed tissues boiled at 1, 3, 5, 10 and 30 min were not infected with WSSV. Mortality data showed that only the positive control (0‐min) treatment displayed high mortality, whereas no mortality was observed in any other treatment category. These findings suggest that cooking shrimp at boiling temperature for at least 1 min might prevent any potential spread of WSSV from endemic countries to other geographical areas where WSSV has not yet been reported.